Experimental and numerical investigation on the non-uniform temperature distribution of thin-walled steel members under solar radiation. (January 2018) - Chen, Deshen; Qian, Hongliang; Wang, Huajie; Chen, You; Fan, Feng; Shen, Shizhao
Abstract: The temperature effect often significantly affects the performance of large-span spatial structure and even becomes one of the controlling loads. To obtain the non-uniform temperature field distribution of the thin-walled steel members under solar radiation and the influence rules of various factors, in this paper, experimental studies are carried out with three groups of specimens including rectangular steel tube, I-shaped steel and circular steel tube. Based on the test data, the non-uniform temperature field distributions considering the influence of solar radiation intensity, member size and surface coating are analyzed in detail. Then, numerical methods for the temperature field of steel members are studied considering multiple environmental factors. The validity of the numerical method is evaluated with test results. Finally, based on the parametrical studies of the major influence factors, a simplified calculation approach is presented for practical engineering applications. The experimental study demonstrates that the non-uniform temperature distribution of steel members truly exists and cannot be overlooked. The numerical method for the temperature field in this paper is effective, and the simplified calculation approach can meet the required engineering precision. The research methods and conclusions of this work can provide valuable references for thermal design, monitoring and control of steel structures. Highlights: Solar temperature field test of steel members is carried out considering various conditions. Non-uniform temperature distribution and influence rules of key factors are obtained. The numerical simulation methods of solar temperature field are verified by the test data. The parametrical study shows the sensitivities of major influence factors. A simplified calculation approach is presented for practical engineering applications.